2011
DOI: 10.1038/pj.2011.51
|View full text |Cite
|
Sign up to set email alerts
|

Cell sheet patterning using photo-cleavable polymers

Abstract: We have found that poly (4-vinylpyridine) (P 4 VP) and poly (methylmethacrylate) thin films can be etched with ultraviolet A (UVA) radiation. Furthermore, we also found that dermal fibroblasts could be cultured successfully on the P 4 VP polymer, with a doubling time comparable to tissue culture Petri dish standards. Consequently, we were able to grow tissue on P 4 VP substrates, this could easily be lifted using UVA radiation. The cell sheets that were removed were then re-plated at a lower density and a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A number of parameters (light intensity, time of exposure and wavelength) can be tuned for a specific target, which allows designing a wide selection of stimuli-responsive ANHs. Photo-responsive, particularly, photo-cleavable polymers, e.g., PNIPA- o -nitrobenzyl alcohol-poly(4-substituted-3-caprolactone) [ 77 ], poly(methyl methacrylate)-poly[poly(ethylene glycol) methyl ether methacrylate] [ 78 ] and P4VP-poly(methyl methacrylate) [ 79 ], have received attention in recent years, since they can be degraded into smaller molecular fragments by irradiation. These photo-responsive polymers are used for the synthesis of ANHs and applied as nano-carriers for drug delivery [ 77 ] and as photodynamic therapeutic agents [ 80 ].…”
Section: Classification Of Anhsmentioning
confidence: 99%
“…A number of parameters (light intensity, time of exposure and wavelength) can be tuned for a specific target, which allows designing a wide selection of stimuli-responsive ANHs. Photo-responsive, particularly, photo-cleavable polymers, e.g., PNIPA- o -nitrobenzyl alcohol-poly(4-substituted-3-caprolactone) [ 77 ], poly(methyl methacrylate)-poly[poly(ethylene glycol) methyl ether methacrylate] [ 78 ] and P4VP-poly(methyl methacrylate) [ 79 ], have received attention in recent years, since they can be degraded into smaller molecular fragments by irradiation. These photo-responsive polymers are used for the synthesis of ANHs and applied as nano-carriers for drug delivery [ 77 ] and as photodynamic therapeutic agents [ 80 ].…”
Section: Classification Of Anhsmentioning
confidence: 99%
“…In addition, P4VP does not require surface treatments and has better uniformity than tissue culture plastic of surface properties. 16 The results indicated that differentiation was determined by the ability of the collagen fibrils formed by the cells to cluster together and form the classical banded collagen fibers. Spuncast flat films and electrospun fiber scaffolds were compared, and banded collagen seemed to form only on the electrospun fibrous substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Poly­(4-vinylpyridine) (P4VP) is a transparent polymer, which is glassy at ambient temperatures (glass transition, T g = 137 °C), and which has been shown to be equivalent to tissue culture plastic for cell culture, supporting adhesion, and proliferation of multiple cells types. In addition, P4VP does not require surface treatments and has better uniformity than tissue culture plastic of surface properties . The results indicated that differentiation was determined by the ability of the collagen fibrils formed by the cells to cluster together and form the classical banded collagen fibers.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address PMMA's limitations, a variety of methods have been investigated in order to enhance cell adhesion on the material by increasing its surface hydrophilicity, including but not limited to chemical-and light-based treatments of the polymer [14][15][16][17]. However, one of the most facile and quick techniques to augment the surface hydrophilicity of a polymer is via air or oxygen plasma treatment.…”
Section: Introductionmentioning
confidence: 99%